Efficacy prediction of neoadjuvant cadonilimab plus FLOT therapy for advanced gastric cancer: a study based on body composition changes - Penghui Liu; Na Li; Jizhen Wang; Lingyun Guo; Jiwu Guo; Guoqing Shi; Jie Mao (Frontiers in Oncology)
ObjectiveThis study aimed. to explore the predictive value of body composition changes in the efficacy of neoadjuvant cadonilimab combined with FLOT therapy for advanced gastric cancer and provide a reference for personalized treatment.MethodsA retrospective study was conducted on 33 patients with advanced gastric cancer who received neoadjuvant cadonilimab combined with FLOT therapy and subsequently underwent surgery. Body composition data were obtained using the InBody 720 body composition analysis device. Based on treatment response, patients were classified into the objective response group and the no-progression group. Quantitative data were presented as median and interquartile range. The Mann-Whitney U test was used for intergroup comparisons, analyzing the relationship between body composition changes before and after neoadjuvant therapy and treatment outcomes.ResultsThe changes in LBM, SLM, SMM, VFA, LEFT ARM SLM, RIGHT ARM SLM, LEFT LEG SLM, RIGHT LEG SLM, TRUNK SLM and IMPEDANCE before and after neoadjuvant therapy showed significant differences (P < 0.05) between two groups, indicating statistical significance. LBM, SLM and SMM showed a decreasing trend in both groups and the reduction was greater in the no-progression group than in the objective response group; VFA expressed a significant reduction in the objective response group, but it tended to increase in the no-progression group; IMPEDANCE showed a significant increase in the objective response group, but the change was insignificant in the no-progression group. SLM in the trunk and limbs showed a decreasing trend in both groups and the reduction was greater in the no-progression group than in the objective response group. The changes in HEIGHT, WEIGHT, BFM, PBF, LEFT ARM MBF, RIGHT ARM MBF, LEFT LEG MBF, RIGHT LEG MBF, TRUNK MBF, WHR and WAIST showed no significant differences (P ≥ 0.05) between two groups, indicating they were not statistically significant.ConclusionsThe changes in LBM, SLM, SMM, VFA and IMPEDANCE can predict the efficacy of neoadjuvant cadonilimab plus FLOT therapy in advanced gastric cancer, especially LBM, SLM and SMM show the highest predictive value. Variations in SLM across different anatomical sites have distinct effects on treatment outcomes, the trunk has the most significant impact, followed by the lower limbs and the upper limbs have the least effect.Trial registrationwww.chictr.org.cn, identifier ChiCTR2200066893.